2006
DOI: 10.1016/j.humimm.2006.08.293
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease and HLA in a Bedouin Kindred

Abstract: We report the prevalence of celiac disease (CD) and its relationship with other autoimmune diseases and HLA haplotypes in a Bedouin kindred. Of 175 individuals sampled and typed for autoantibodies and HLA class II genotypes, six (3.4%) members had CD and an additional ten (5.7%) members tested positive for autoantibodies to transglutaminase (TgAA+). Several CD/TgAA+ relatives also had islet cell antigen or adrenal autoimmunity. Affected relatives are more closely related than expected from the pedigree relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
(53 reference statements)
0
7
1
1
Order By: Relevance
“…12,[34][35][36] We previously reported significant clustering and coclustering of islet and celiac autoimmunity in the kindred, explained in part by a common association with DR3-DQ2, which was present in all of 16 relatives with celiac autoimmunity. 37 Interestingly, the frequency of DR3-DQ5 was higher among relatives with celiac autoimmunity compared to unaffected relatives with DR3-DQ2 (0.19 vs 0.05 among DR3-DQ2 relatives with and without celiac autoimmunity), although the difference was not statistically significant (Po0.10) and there was no difference in the distribution of class II haplotypes between relatives with celiac disease and relatives with celiac-related autoantibodies without celiac disease. Nevertheless, the results are consistent with the hypothesis that DR3 is primarily responsible for the association of celiac and islet autoimmunity in the kindred whereas DQ2 determines more specific aspects of phenotypic expression including the manifestation, age of onset and severity of autoimmune disease.…”
Section: Differential Effects Of Dr and Dqmentioning
confidence: 84%
“…12,[34][35][36] We previously reported significant clustering and coclustering of islet and celiac autoimmunity in the kindred, explained in part by a common association with DR3-DQ2, which was present in all of 16 relatives with celiac autoimmunity. 37 Interestingly, the frequency of DR3-DQ5 was higher among relatives with celiac autoimmunity compared to unaffected relatives with DR3-DQ2 (0.19 vs 0.05 among DR3-DQ2 relatives with and without celiac autoimmunity), although the difference was not statistically significant (Po0.10) and there was no difference in the distribution of class II haplotypes between relatives with celiac disease and relatives with celiac-related autoantibodies without celiac disease. Nevertheless, the results are consistent with the hypothesis that DR3 is primarily responsible for the association of celiac and islet autoimmunity in the kindred whereas DQ2 determines more specific aspects of phenotypic expression including the manifestation, age of onset and severity of autoimmune disease.…”
Section: Differential Effects Of Dr and Dqmentioning
confidence: 84%
“…40 However, in this analysis, we saw no evidence for linkage to HLA across the 18 pedigrees. Eller et al 15 performed a genome-wide linkage analysis of one large Bedouin pedigree with CD and also did not find evidence of linkage to the HLA region. They hypothesized that the high frequency of the CDassociated haplotypes resulted in an inability to determine alleles that are identical by descent versus by state, reducing the power to detect linkage.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, individual III: 10 carried both the high-risk HLA-DQ2.5 and the CD59 variant, but still he was phenotypically normal. This suggests that other genetic and/or environmental factors, besides HLA and the CD59 A recent study performed in Bedouin kindred also reported absence of linkage to the HLA locus, where a higher frequency of high-risk HLA alleles was observed in affected members, thus negative linkage was probably because of a lack of distinction between alleles that were identical by descent from those that were identical by state (5). Besides this, there could be various reasons why we failed to detect linkage at the HLA locus including low marker density (closest marker D6S1051 being approximately 4 cM away), no difference in the inheritance pattern of HLA alleles between affected/nonaffected members and because in this family risk for disease was increased by HLA alleles being in trans and not in cis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of linkage and association studies have been carried out to try to identify genes that might increase the individual's susceptibility for CD. The human leukocyte antigen (HLA) locus on chromosome 6 was the most commonly reported locus (2)(3)(4), although, recently, linkage to this region was not confirmed in a large Bedouin family (5). Other chromosomal loci were identified by genomewide linkage scans including 5q31-q33 (6), 10q23, 15q26, 16q23, 19p13.1, 6p12, 2q and 11p11 (7)(8)(9), with the latter being further confirmed in a later study (10).…”
Section: Introductionmentioning
confidence: 99%